No radiographic index predicts difficult intubation using the Optiscope™ in cervical spine surgery patients: a retrospective study - Hyongmin Oh; Hansol Kim; Hyun-Kyu Yoon; Hyung-Chul Lee; Hee-Pyoung Park (BMC Anesthesiology, 2020)
Abstract Background The Optiscope™ can be used for intubation with minimal neck motion. We retrospectively investigated radiographic predictors of difficult intubation using the Optiscope™ by analyzing preoperative radiographic images. Methods One hundred eighty-four patients who were intubated with the Optiscope™ under manual in-line cervical stabilization for cervical spine surgery were enrolled. Radiographic indices were measured on preoperative cervical spine lateral X-ray and magnetic resonance imaging images. Difficult intubation was defined as failure or time consumption more than 90 s on the first attempt. To identify significant predictors of difficult intubation using the Optiscope™ and evaluate their diagnostic value, multivariable logistic regression and receiver operating characteristic analyses were used. Results Fourty-seven patients showed difficult intubation. There was no significant difference in radiographic indices between the difficult and easy intubation groups, but higher body mass index (BMI) (26.5 [3.0] vs. 24.6 [3.5] kg/m2, P = 0.001), shorter sternomental distance (SMD) (122.0 [104.0 to 150.0] vs. 150.0 [130.0 to 170.0] mm, P = 0.001), shorter interincisor gap (40.0 [35.0 to 45.0] vs. 43.0 [40.0 to 50.0] mm, P = 0.006), and higher incidence of excessive oral secretions (10.6% vs. 2.9%, P = 0.049) were observed in patients with difficult intubation. In multivariable analysis, BMI (odds ratio [95% confidence interval]; 1.15 [1.03 to 1.28], P = 0.011) and SMD (odds ratio [95% confidence interval]; 0.98 [0.97 to 1.00], P = 0.008) were associated with difficult intubation with the Optiscope™. In receiver operating characterstic analysis, the area under the curve for body mass index was 0.68 (95% confidence interval; 0.60 to 0.77, P < 0.001) and that for sternomental distance was 0.66 (95% confience interval; 0.57 to 0.75, P = 0.001). Conclusions The incidence of difficult intubation using the Optiscope™ under manual in-line cervical stabilization was 25.5% in cervical spine surgery patients. No significant predictor of difficult intubation with the Optiscope™ was identified among the measured radiographic indices. Although high BMI and short SMD were predictive of difficult intubation with the Optiscope™, their discrimination power was weak.